Germs are not for sharing - Verdick, Elizabeth; Heinlen, Marieka (Minneapolis, MN : Free Spirit Pub., 2006)
Describes what germs are and what they can do
Keywords: Hygiene -- Juvenile literature; Bacteria -- Juvenile literature; Cleanliness; Bacteria